Influence of scaler tip design on root surface roughness, tooth substance loss and patients' pain perception: an in vitro and a randomised clinical trial - Nur Ayman Abdul Hayei; Noor Azlin Yahya; Syarida Hasnur Safii; Roslan Saub; Rathna Devi Vaithilingam; Nor Adinar Baharuddin (Springer Nature, 2024)
Indexed by WOS/SCOPUS/ERA